Analisis Perilaku Mahasiswa dalam Penggunaan Quick Response Code Indonesian Standard (QRIS) untuk Transaksi Pembayaran di Kantin Kampus UIN Sulthan Thaha Jambi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze student behavior in using the Quick Response Code Indonesian Standard (QRIS) as a payment method at the UIN Sulthan Thaha Saifuddin Jambi canteen, focusing on students’ perceptions and the benefits they experience from using QRIS. The background of this research is based on the phenomenon of the growing use of digital payment systems on campus, in line with the government’s program to accelerate financial inclusion and promote a cashless lifestyle among the younger generation.This research employs a qualitative descriptive method, with data collected through in-depth interviews with 25 informants, consisting of active UIN Sulthan Thaha Saifuddin Jambi students who have used QRIS at the campus canteen. The data were analyzed descriptively, referring to consumer behavior theory and the Diffusion of Innovation Theory to understand students’ behavioral patterns in adopting and using QRIS. The results indicate that most students have a positive perception of QRIS. They consider QRIS as a more modern, practical, and efficient payment method that helps reduce queues in the canteen. Students also experience tangible benefits from using QRIS, such as the convenience of making payments without carrying cash, better security by reducing the risk of losing money, and automatic transaction records that assist them in managing expenses. However, the intensity of QRIS usage varies; some students use it regularly, while others use it occasionally, although both groups acknowledge its benefits. In conclusion, the implementation of QRIS in the campus canteen has brought positive impacts for students, both in terms of convenience and in supporting a cashless lifestyle. This study is expected to serve as input for the campus in strengthening the digitalization of non-academic services and encouraging students to be more adaptive to the development of digital financial technology.